The creation of a permanent establishment in South Africa as a result of the activities or presence of a partner or partners in South Africa - Van Schalkwyk, Esther Maria (Department of Finance and Tax, 2017)
This dissertation seeks to establish whether the presence or activities of a partner or partners in South Africa creates (or is at risk of creating) a permanent establishment for that partner, the partnership or the co-partners in South Africa. At the outset, the major legal and fiscal consequences of a partnership under South African law are investigated. The unique legal and fiscal treatment of a partnership as a mere aggregate of persons that is treated as fiscally transparent under South African law is relevant to determine the potential application of double taxation agreements to partnerships or their partners. Once the terms of a double taxation agreement are found to apply in the circumstances, the creation of a permanent establishment in terms thereof becomes relevant. The different types of partnerships and partners under South African partnership law are set out and their differentiating characteristics analysed in an effort to identify whether the activities or presence of certain partners are more at risk of giving rise to a permanent establishment than others. In a commercial context, the important distinction is drawn between ordinary and extraordinary partners as very different commercial consequences attach to these partners. In particular, whereas ordinary partners automatically derive an implied authority or mutual mandate to manage the business of the partnership as agents of their co-partners by virtue of the partnership agreement, extraordinary partners are excluded from the mutual mandate. The implied authority amongst partners becomes particularly relevant when considering one of the alternative tests for creating a permanent establishment that appear in the prevalent model tax conventions commonly used in the South African context, in terms of which the existence of authority is one of the required elements for the creation of a permanent establishment. The special rules surrounding the source of partnership income is investigated as a means of establishing jurisdiction to tax under South African domestic source rules. The impact of legislation on the South African source rules pertaining to partnerships as developed under the common law is critically analysed and the relevance of source rules in the permanent establishment context is evaluated. It is submitted that it is premature to consider the rules surrounding the creation of a permanent establishment under the terms of a double taxation agreement before it is established that the relevant contracting state has the requisite jurisdiction to tax and furthermore that the terms of that double taxation agreement apply to the matter at hand. Finally, the relevant articles of the model tax conventions commonly used in the South African context are discussed with specific focus on the unique attributes of a partnership that may impact on the creation of a permanent establishment for the partner or partners by virtue of the presence or activities of a partner or the partners in South Africa. The risk of creating a permanent establishment by virtue of the presence or activities of an ordinary partner in South Africa is contrasted with that of an extraordinary partner. It is concluded that the activities or presence of ordinary partners (as opposed to extraordinary partners) are particularly at risk of creating a permanent establishment in South Africa, although it is acknowledged that certain requirements will have to be met on the facts of each case before a permanent establishment will be found to exist.